Towards Measuring the Degree of Fulfillment of Service Level Agreements - Schulz, Frank (2010 Third International Conference on Information and Computing, 2010)
In service oriented architectures (SOA), the non-functional properties of services have been recognized to be highly important in addition to the functionality of services as a means to differentiate services according to quality considerations. Service level agreements (SLAs) are formalized contracts between service providers and service consumers that are used to define quality of service (QoS) properties. The violation of an SLA by the service provider typically results in a penalty to compensate the service consumer. In order to avoid such situations, the service provider needs to recognize critical service instances and to take appropriate countermeasures before a violation happens. Therefore a measure for quantifying the danger of SLA violation is needed as part of a service level management system. This paper proposes a concept for the definition and evaluation of such a metric that takes into account the underlying structure of the SLA as well as the available options for monitoring service quality parameters. Hence it becomes possible to obtain detailed information of the status of service fulfillment at runtime and to identify critical service instances. The methodology is exemplified with the availability property.